2019
DOI: 10.4103/jisp.jisp_612_18
|View full text |Cite
|
Sign up to set email alerts
|

Periodontally accelerated osteogenic orthodontics combined with recombinant human bone morphogenetic protein-2: An outcome assessment

Abstract: Context: Periodontally accelerated osteogenic orthodontics (PAOO) combines alveolar corticotomy, bone graft materials, and the application of orthodontic forces for rapid correction of malocclusions. Aims: The present study aims to primarily assess differences in orthodontic treatment duration, bone quality around corticotomy sites, postoperative healing, and subjective pain when corticotomy was done conventionally and with the placement of recombinant human bone morpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…Six trials evaluated the decrowding of lower and/or upper anterior teeth [ 17 , 19 , 29 , 31 - 33 ]. Four of them included non-extraction treatment with minimal to moderate maxillary and/or mandibular anterior crowding [ 17 , 28 , 29 , 32 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Six trials evaluated the decrowding of lower and/or upper anterior teeth [ 17 , 19 , 29 , 31 - 33 ]. Four of them included non-extraction treatment with minimal to moderate maxillary and/or mandibular anterior crowding [ 17 , 28 , 29 , 32 ].…”
Section: Reviewmentioning
confidence: 99%
“…Allograft was employed in two trials [ 29 , 30 ], xenograft in two trials [ 17 , 19 ], synthetic bone substitutes in four trials [ 17 , 18 , 28 , 32 ] and composite grafts in one trial [ 31 ]. Regarding the primary outcomes, eight articles assessed the duration of orthodontic treatment [ 17 - 19 , 28 - 32 ], three articles assessed bone density using periapical radiographs [ 17 , 31 ] or panoramic radiographs [ 32 ], and one article assessed the alveolar thickness using a CT scan [ 27 ]. On the other hand, the secondary outcomes included clinical probing depth assessment in three studies and were dependent on using a periodontal probe [ 17 , 29 , 32 ].…”
Section: Reviewmentioning
confidence: 99%
“…The pain was severe on the first day due to trauma and edema as a result of the surgery. Also, 25% of patients had severe pain and took painkillers heavily during the first week following surgery; whereas a clinical trial by Chandra et al showed that the pain level was moderate immediately after surgery in the PAOO group compared to the traditional corticotomy group without any significant difference between them [ 19 ]. It should be noted that Chandra et al assessed the level of pain immediately after surgery and this did not reflect the actual pain level due to the persistence of the local anesthetic effect.…”
Section: Discussionmentioning
confidence: 99%
“… 4 The resulting pro-inflammatory mediators, e.g., H + and BMP-2, on one hand initiate local bone remodeling and on the other hand bond to nerve terminals to elicit painful sensations and mechanical hyperalgesia. 12 , 15 , 16 Tooth mechanical hyperalgesia is the most prominent symptom associated with tooth movement, manifested with biting or chewing pain and masticatory disturbance. 3 In our previous study, we invented the methods of using bite force for the evaluation of mechanical hyperalgesia induced by tooth movement and validated the viability and reliability of this method.…”
Section: Discussionmentioning
confidence: 99%